PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA KIT PADA PEMBELAJARAN MATEMATIKA DI KELAS VII SMP NEGERI 2 ELLA HILIR - Supardi, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The objective of the research was to improve students’ mathematic learning outcomes. This research was a classroom action research with descriptive method approach. Subjects of this research were 7th grade students of SMPN 2 Ella Hilir on 2015/2016 academic year consisting of 25 students. Based on the result of the research it could be concluded that students’ learning outcomes on mathematic learning was increased by using lesson with KIT media. First cycle percentage was 60% and on second cycle percentage there were improvement from 12% to 72%. There were improvement on students’ learning outcomes so a lesson with application of KIT media can improve learning outcomes of 7th grade students of SMPN 2 Ella Hilir.Keywords : KIT media, mathematic learning outcomes